Pembuatan Media Pembelajaran Pada Elemen Estimasi Biaya Pekerjaan Konstruksi Dan Perumahan Di SMK Negeri 2 Kota Solok - Rivky Syafelmi; Henny Yustisia (Jurnal Vokasi Mekanika (VoMek), 2025)
This research is based on the lack of variation in the learning media used by students in the learning process on the element of estimating the cost of construction and housing work, students have difficulty understanding the material for calculating the volume of work, there is no variety of learning media based on audio visual videos, and the learning methods used have not been able to overcome the difficulties of students. To overcome the existing problems, an audio-visual video-based learning media was developed with the help of sketchup software and wondershare filmora on the work volume calculation material. The purpose of this research is to develop a valid and practical audio-visual video-based learning media product. This type of research is Research and Development (R&D) with a 4D development model. Then after being declared valid, a product practicality test was carried out by 12 students of class XI of TKP. The final result of the validation of the material expert obtained a score of 0.82 with the category "very valid" and the final result of the validation of the media expert obtained a value of 0.80 with the category "valid". The final result of the student practicality test obtained a score of 86% in the category of "very practical". Based on the results obtained, it can be concluded that the video-audio visual based learning media on the work volume calculation material developed is valid and practical for use by students of class XI of TKP at SMK Negeri 2 Solok City.